Quality of Service and Value for Money in West Bandung Tourist Destinations - Sukmawan, Nazwa (STKIP Singkawang, 2024)
One of the strategic efforts in maintaining visitor satisfaction and loyalty can be done by maintaining the Quality of Service which should be a good quality of service commensurate with the Value of Money that visitors have given. This study aims to explore the extent of the level of visitor satisfaction with the Quality of Service and Value for Money in tourist destinations in the West Bandung area. This research used a quantitative method. Respondents who provided information in this study were tourists who met the requirements as respondents to be able to fill out and provide the information needed when filling out the questionnaires. The number of respondents was 220 people with the composition of Lembang Park Zoo 73 visitors, the Great Asia Africa 73 visitors, and the Floating Market 73 visitors. The analytical techniques used in this study were measured using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The results showed that based on the CSI (Customer Satisfaction Index) of 79.09% visitors to tourist destinations in the West Bandung area felt (Satisfied). Based on the gap analysis (GAP), the analysis obtained is with a performance score value of 86.96 smaller than the expected score of 88.15 so the level of performance of service quality and value for money is still far from the expectations of visitors to tourists destinations in West Bandung. The results of this research can be used as material for consideration and evaluation of the quality of service and value for money that has been developed.